(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2024)
In the 1990’s Neil McLynn redefined Ambrose of Milan as a manipulative politician who used the new state religion as a vehicle to broker personal power and influence. This view acknowledged the potential tension between the teachings of early Christianity and the prevailing pragmatism of an age where Christianity became a privileged religion. Although McLynn’s view has been regarded persuasive from a modern point of view, it largely built on supposition rather than Ambrose’s work in a textual and contemporary historical context (primary and secondary sources of Late Antiquity). Careful exploration of these sources shows that, like earlier fathers of the Church, Ambrose showed himself a man of principle and self-denial, who operated from the premise of the Scriptures as God’s authoritative voice for past and present. Secondary sources from Late Antiquity confirm that he was also recognized by his contemporaries as such. A philological investigation of Ambrose’s magnum opus on ethics, De Officiis, considers Ambrose’s views on authority and human thought and behaviour. From a moral perspective, Ambrose argues that his office of bishop is principally a teaching office, not to promote personal interest, but to pass on the oracles of God for human life, the teachings of Scripture. While the church father also identifies practical tensions, he sets forth the Divinas Scripturas as guiding principle for Christian ethics and per implication for all of humanity, as he considers all the world under the claim of its Creator and Lord. Christ is entitled to the obedience of all. Historically this is evidenced in Ambrosius’s endeavours to use his influence with Roman emperors to change the imperial laws towards Divine law, i.e., to Christianize society. Building on Bartelink and Davidson, a linguistic analysis of De Officiis shows Scripture authority to be the determining factor for Ambrose’s ethics. Ambrose did not think opportunistically, but subjected to external accountability in determining what was right and wrong. This hypothesis acknowledges Ambrose’s specific personality and gifted political background, but suggests that rather than self-interested Machiavellianism, Scripture was the guiding moral principle for his goals and actions.